Gene Therapy for Coagulation Disorders. Issue 9 (29th April 2016) - Swystun, Laura L.; Lillicrap, David
Abstract : Molecular genetic details of the human coagulation system were among the first successes of the genetic revolution in the 1980s. This information led to new molecular diagnostic strategies for inherited disorders of hemostasis and the development of recombinant clotting factors for the treatment of the common inherited bleeding disorders. A longer term goal of this knowledge has been the establishment of gene transfer to provide continuing access to missing or defective hemostatic proteins. Because of the relative infrequency of inherited coagulation factor disorders and the availability of safe and effective alternative means of management, the application of gene therapy for these conditions has been slow to realize clinical application. Nevertheless, the tools for effective and safe gene transfer are now much improved, and we have started to see examples of clinical gene therapy successes. Leading the way has been the use of adeno-associated virus–based strategies for factor IX gene transfer in hemophilia B. Several small phase 1/2 clinical studies using this approach have shown prolonged expression of therapeutically beneficial levels of factor IX. Nevertheless, before the application of gene therapy for coagulation disorders becomes widespread, several obstacles need to be overcome. Immunologic responses to the vector and transgenic protein need to be mitigated, and production strategies for clinical grade vectors require enhancements. There is little doubt that with the development of more efficient and facile strategies for genome editing and the application of other nucleic acid–based approaches to influence the coagulation system, the future of genetic therapies for hemostasis is bright.